2012
DOI: 10.1345/aph.1q512
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Preventive Care Measures of Indigent Diabetes Patients Within a Pharmacist-Managed Insulin Titration Program vs Standard Care

Abstract: Pharmacist-provider collaboration can result in significant clinical improvements, including A1C reduction and adherence to preventive care measures, when compared to standard care in a medically underserved population with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…Clinical Pharmacist Specialists, who have prescribing privileges and work within collaborative practice agreements with primary care or internal medicine physicians, have optimized clinical outcomes for patients with common metabolic disorders, including diabetes. [8][9][10][11][12][13] The Diabetes Intense Medical Management (DIMM) "tune up" clinic was created as a collaborative pharmacist-endocrinologist medication therapy management (MTM) clinic to manage complex type 2 diabetes (T2D) patients and help them achieve metabolic goals (glycosylated hemoglobin [A1C], hypertension [HTN], lipid, weight) within 6 months. 14 Overseen by an endocrinologist at a Veterans Affairs medical center, the DIMM clinic used a short-term model that coupled personalized clinical care with real-time, patient-specific diabetes education during an average of three 60-minute visits over 6 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical Pharmacist Specialists, who have prescribing privileges and work within collaborative practice agreements with primary care or internal medicine physicians, have optimized clinical outcomes for patients with common metabolic disorders, including diabetes. [8][9][10][11][12][13] The Diabetes Intense Medical Management (DIMM) "tune up" clinic was created as a collaborative pharmacist-endocrinologist medication therapy management (MTM) clinic to manage complex type 2 diabetes (T2D) patients and help them achieve metabolic goals (glycosylated hemoglobin [A1C], hypertension [HTN], lipid, weight) within 6 months. 14 Overseen by an endocrinologist at a Veterans Affairs medical center, the DIMM clinic used a short-term model that coupled personalized clinical care with real-time, patient-specific diabetes education during an average of three 60-minute visits over 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical Pharmacist Specialists, who have prescribing privileges and work within collaborative practice agreements with primary care or internal medicine physicians, have optimized clinical outcomes for patients with common metabolic disorders, including diabetes. 8-13…”
Section: Introductionmentioning
confidence: 99%
“…Four studies of pharmacist care management collectively reduced the HbA1C when compared to the control intervention (MD −0.76, 95% CI −0.93 to −0.59) from a baseline of 9.81 ( Figure 3 ). 27 30 Jameson et al had no impact on the HbA1C from a baseline of at least 9 and was excluded from the analysis because it reported skewed data. 31…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps one of the most important periods when a patient with diabetes requires support is during the initiation and titration of basal insulin. A retrospective cohort study in the USA showed that, compared with physician management alone, a pharmacist-managed insulin-titration program resulted in significantly greater HbA1c reductions, with a greater proportion of patients adhering to recommended preventive care measures [24]. Although guidelines state that most patients can be taught to titrate their own insulin dose using simple algorithms, they also point out that frequent contact may be necessary during this period [2].…”
Section: Role Of the Pharmacist In Diabetes Carementioning
confidence: 99%